HLA-DRB1 frequencies of the Comorian population and their genetic affinities with Sub-Saharan African and Indian Oceanian populations - (:unkn) unknown (My University, 2006)
Background: Ethnic-historic sources have considered the Comorian population to be the result of an amalgamation of African, Arabian and Southeast Asian groups. Aim: This study seeks to determine the genetic relationships and contributions from Sub-Saharan Africa and Indian Oceania and to reconstruct past migration events. Subjects and methods: The human leukocyte antigen (HLA) polymorphism of a Comorian population was described and analysed. Results: Genetic distances and multidimensional scaling analyses showed complex patterns of genetic differentiation in the Indian Oceanian area as a result of continuous gene flow occurring within the past 2500 years. Nevertheless, the Comorian genetic pool appears to be a mix of Bantu-speaking and Arab populations as testified to by admixture estimations of almost 50-60% and 27-33%, respectively. Conclusion: The Comorian population may represent the eastern limit of the recent and massive eastward Bantu expansion. In contrast to the population from Madagascar (Merina), only a restricted influence of Austronesian populations was found.
Keywords: African Research